2018
DOI: 10.1080/01576895.2018.1558407
|View full text |Cite
|
Sign up to set email alerts
|

Institutional readiness for digital archives management at United States International University-Africa

Abstract: This article seeks to assess the readiness of the United States International University-Africa (USIU-A) to manage digital archives with a view to proposing strategies to enhance digital archives management at the institution. The study was informed by the Records Continuum Model, the Open Archival Information System Model and the Digital Curation Centre Lifecycle Model. A case study was used as part of a mixed-method research approach with a sample size of 120 respondents drawn from a population of 6937 by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…A number of other studies have similarly registered shortcomings in the ICT infrastructure necessary for the management of e-records. Most notably, a study done by Odhiambo (2018) observed that the equipment required for the management of digital archives (e-records of enduring value) at the United States International University in Kenya was not up to standard. This finding shows that ICT-related challenges are common not only in Malawi but other countries as well hence need concerted effort to solve them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of other studies have similarly registered shortcomings in the ICT infrastructure necessary for the management of e-records. Most notably, a study done by Odhiambo (2018) observed that the equipment required for the management of digital archives (e-records of enduring value) at the United States International University in Kenya was not up to standard. This finding shows that ICT-related challenges are common not only in Malawi but other countries as well hence need concerted effort to solve them.…”
Section: Resultsmentioning
confidence: 99%
“…These e-government transactions lead to the generation of e-records that serve as proof of those activities. The proliferation of e-government initiatives in various sectors of the economy has resulted in huge amounts of electronic information and records being created on a daily basis (Odhiambo, 2018). Whilst some of this information is born digital (electronic), some of it is primarily produced in printed format and is converted into electronic format over time through the process of digitisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A random sampling method was utilized for selecting fifty registry staff in different sections within the university. Odhiambo [13] evaluated the readiness of USIU-A for managing digital archives to propose a strategy for enhancing digital archive management at the organization. The research shows that the organization needing for digital archive management was not up to standard.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kearsipan merupakan sekumpulan surat yang tercatat dan bilamana dibutuhkan bisa dengan cepat ditemukan (Rumakat, 2018), sedangkan penulis akan merancang dan membangun sistem earchives dengan tujuan untuk memudahkan arsiparis dalam memperoleh data yang diinginkan. Effective digital management is reflected in the scope, priorities and resources an organisation develops and adopts to explicitly guide its decision and practices in digital archives management (Odhiambo, 2018). Manajemen kearsipan digital merupakan pengelolaan data arsip surat dalam suatu organisasi atau instansi.…”
unclassified